Learning a mixture of graph neural networks - Lai, Yu-Shiang (Nanyang Technological University, 2023)
GNN models are designed to handle complex and non-uniform graph-structured data for classification tasks such as node, link, and graph-level predictions. However, the randomness and unfixed node ordering of graph data still proposes a challenge to GNN models. To improve the accuracy of GNN models, this study proposes a mixture model approach that combines multiple renowned GNN architectures to produce a single output. The study discusses the advantages of several GNN architectures and tests the models on selected benchmark datasets to examine their validity. By comparing simple GNN models to mixture models, the study hopes to provide insights into the development of more accurate GNN models.